Metacognitive Skills Among Technical Student Through Mathematical Problem Solving: : Technical Students’ Perceptions - Wan Muda, Wan Hanim Nadrah; Ab Halim, Fazlinda; Ismail, Nurtasnim; Mohd Jimas, Mohd Norhafidz (Online Journal for TVET Practitioners, 2019)
Abstract: This study was conducted to identify metacognitive skills consisting of monitoring skills, evaluating skills and regulating skills among TVET students in problem solving of mathematic subject. The cognitive development of university students to solve the problem is an important factor in education. Metacognitive is a set of cognitive skills and process to our mind to think deeply and critically on the task. Survey questionnaire was used to collect the data of 135 respondents. Descriptive and inferential statistics was employed to analyze the data. The means score of respondents’ metacognitive skills were investigated. The results show that respondents have high metacognitive skills in solving mathematical problems. Monitoring skills are the dominant among the three metacognitive skills. From the T-test (independent sample T-Test), there was no significant difference in metacognitive skills across gender. In conclusion, students have high metacognitive skills and need to be applied in the teaching and learning process to improve their result in mathematical subjects.